The Meaning and Function of Ornaments in Bridal Make-Up in Terms of the Boh Gaca Tradition in Beutong Sub-District, Nagan Raya District, Aceh Province - Arlinawati, Arlinawati; Daryusti, Daryusti (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the philosophical meanings and functions of ornaments in bridal makeup based on the Boh Gaca tradition in Beutong District, Nagan Raya Regency, Aceh Province. Boh Gaca is a ritual of applying henna with distinctive motifs passed down through generations. The study employs ethnographic methods with a qualitative descriptive approach to explore the symbolic meanings and cultural values embedded in these ornaments. Levi Strauss's structuralism theory serves as the main framework, supported by Clifford Geertz's symbolism theory, Bronislaw Malinowski's functionalism, and Edward Shils's theory of cultural preservation.The findings reveal that Boh Gaca motifs, such as geometric patterns and floral designs, carry deep philosophical meanings, symbolizing harmony, fertility, and hopes for a happy household. This tradition also serves as a symbol of social status and cultural identity for the Acehnese community. The younger generation plays a crucial role in sustaining this tradition, despite facing challenges such as lack of interest, modernization influences, and limited educational media. Innovation and intergenerational collaboration, along with the use of social media, are key strategies in maintaining the existence of Boh Gaca. The conclusion of this study affirms that Boh Gaca is not merely an aesthetic ornament, but a cultural heritage rich in symbolic and social values that must continue to be preserved.